Coaching-Based Academic Supervision Strategy by The Principal in Improving Teacher Competence to Design Deep Learning at SD IT Robbani Ogan Ilir - Fitrianti; Yasir Arafat; Mulyadi (Graduate Program Magister Manajemen Pendidikan, 2026)
The purpose of this study is to describe the coaching-based academic supervision strategy employed by the principal in an effort to enhance teacher competence in designing deep learning at SD IT Robbani, Ogan Ilir. This research utilizes a qualitative approach with a case study design. The instruments and data collection techniques include in-depth interviews, observation, and documentation study. Data analysis was conducted using the Interactive Model by Miles, Huberman, and Saldaña. Informants were selected using purposive sampling. Supervision planning began with data-driven needs identification to build psychological safety for educators. The implementation of coaching adopted the TIRTA framework, which stimulated teachers' intrinsic motivation and self-reflection. Evaluation results demonstrate a significant improvement in teachers' ability to develop instructional designs, although reaching the highest cognitive level (C6) remains a challenge due to student heterogeneity. This research is applicable and practically beneficial in the fields of educational management, instructional leadership, and continuous professional development for principals and teachers. The novelty of this study lies in its specific examination of the synergy between coaching intervention by the principal and the improvement of teachers' competence in designing deep learning documentation, by shifting the paradigm from instructive evaluation to collaborative mentoring within a school environment that integrates Islamic values.